2015
DOI: 10.3126/ije.v4i1.12186
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Organic Carbon Stock of Temperate Coniferous Forests in Northern Kashmir

Abstract: Soil organic carbon (SOC) estimation in temperate forests of the Himalaya is important to estimate their contribution to regional, national and global carbon stocks. Physico chemical properties of soil were quantified to assess soil organic carbon density (SOC) and SOC CO 2 mitigation density at two soil depths (0-10 and 10-20 cms) under temperate forest in the Northern region of Kashmir Himalayas India. The results indicate that conductance, moisture content, organic carbon and organic matter were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The average basal area reported in all forests stands was 47.35 m 2 ha − 1 ; (ranged between 15.4 m 2 ha − 1 and 74.49 m 2 ha − 1 ). These values are more or less comparable with the earlier reports from Garhwal .46 m 2 ha − 1 ), from temperate forests of Northern Kashmir .98 m 2 ha − 1 ), from moist tropical montane of the Himalaya by Malik and Bhatt (2015), 492 Nha − 1 in subtropical forest of Pakistan Himalaya by Shaheen et al (2016), 578 Nha − 1 from Western Himalaya by Dar and Sahu (2018), 390-433 Nha − 1 from Saptasajya hill range, India, by Sahu et al (2019) and higher than other region of western Himalayas 90-302 Nha − 1 by Shaheen et al (2012). Similarly, the average 90.99 Nha − 1 was reported by Shaheen et al (2016) in forest of Kashmir Himalaya and 149.99 Nha − 1 was reported by Akash and Bhandari (2019) from Garhwal Himalaya, India, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The average basal area reported in all forests stands was 47.35 m 2 ha − 1 ; (ranged between 15.4 m 2 ha − 1 and 74.49 m 2 ha − 1 ). These values are more or less comparable with the earlier reports from Garhwal .46 m 2 ha − 1 ), from temperate forests of Northern Kashmir .98 m 2 ha − 1 ), from moist tropical montane of the Himalaya by Malik and Bhatt (2015), 492 Nha − 1 in subtropical forest of Pakistan Himalaya by Shaheen et al (2016), 578 Nha − 1 from Western Himalaya by Dar and Sahu (2018), 390-433 Nha − 1 from Saptasajya hill range, India, by Sahu et al (2019) and higher than other region of western Himalayas 90-302 Nha − 1 by Shaheen et al (2012). Similarly, the average 90.99 Nha − 1 was reported by Shaheen et al (2016) in forest of Kashmir Himalaya and 149.99 Nha − 1 was reported by Akash and Bhandari (2019) from Garhwal Himalaya, India, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies related to tree biomass and carbon content have been conducted across the world by Nowak and Crane (2002), Nowak et al (2013), Fares et al (2017, Brack (2002), Kiran and Kinnary (2011), Ugle (2010), Velasco et al (2016), Nowak et al (2007) and Zhao (2015) etc. Similarly, few studies in Jammu and Kashmir on forest biomass and carbon have been carried out by Dar and Sundarapandian (2015), Wani et al (2017), Handa et al (2017), Dar and Sahu (2018), Gairola et al (2020) while, few studies on biomass and carbon sequestration potential of trees of forest area, outside forest area, urban and of sacred grooves were investigated by Jasrotia and Raina (2017), Sharma et al (2020), Mahajan et al (2021), Devi (2017), Kour and Sharma (2017), Ahmed and Sharma (2018), Bhat et al (2019) and Priya and Sharma (2018). So, keeping in view the importance of tree vegetation in urban habitat our main aim of the study was to evaluate the carbon content and sequestration potential of urban trees especially in an institution to understand and to comply with aim of sustainable living.…”
Section: Introductionmentioning
confidence: 99%
“…According to Birhanu (2017), larger biomass in natural forest might be attributed to maturity, species diversity, good understory cover, tree size, density, species composition, forest age and protection level, all of which determine the forest's C storage level Dar and Sahu (2018). also reported that the variation in the carbon stock of forest ecosystems can be related to forest age, forest types and topography.…”
mentioning
confidence: 99%